Utilización de subproductos de cosecha (choclo, habas, arveja y brócoli) en la alimentación de cuyes en la parroquia de Cusubamba del cantón Salcedo provincia de Cotopaxi. - Vivanco Aguayo, Alicia Mariela (2019)
Guinea pigs with an age of 15 days and up until the end of the fattening stage will be used, lasting 60 days (8 weeks) between the months of November, December and January. Harvest by-products will be supplied in the diet of the guinea pigs, which are discarded or provided for other animals that do not know how to take full advantage of them, these are the wastes of corn, beans, peas and broccoli, the treatments in turn will be valued one to one since each treatment has 5 repetitions, during the present investigation the following variables such as: weight, weight gain, feed conversion and mortality were evaluated